The phenomenon of “celebrity ustadz” in Indonesia on the ethics of dakwahtainment - Bahri, Media Zainul (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
One of the most striking trend of ‘Popular Islam’ in Indonesia is the emerging of celebrity ustadz within the last decade. This phenomenon portrays a modern and fashionable Islam, however, it is also fears to degrade virtuous values of ustadz. This phenomenon appears prominently along with the political reformation in Indonesia in the late of 1990s. The emerging celebrity ustadzs with glamorous life-style and highly exposure to public have changed not merely the image of ustadz and the interaction pattern between ustadz and the followers (umma), but also gave rise what the so-called “dakwahtainment.” Now, here is the interaction between ustadz (like an idol-artist) with his fans or followers. This trend also represents an ideal blend between religion (Islam), television industry, and capitalism. The commodification of Islam is obvious, with superficial actors, producers, and consumers. From both, the measure of the ethics of Ulamaship (traditional clerical moral qualifications) and ethics of dakwah, the phenomenon of ustadz celeb is a new Islamic culture that is unethical. Therefore, many Indonesian Muslims, especially Muslim intelligentsia, were very disappointed. In fact, it causes a lot of cynicism. The ustadz profession, especially celebrity ustadz, is now considered “low”, and the only thing that is “high” seem to be their rate and theirlife style.